2019
DOI: 10.3389/fphys.2019.01360
|View full text |Cite
|
Sign up to set email alerts
|

Menthol as an Adjuvant to Help Athletes Cope With a Tropical Climate: Tracks From Heat Experiments With Special Focus on Guadeloupe Investigations

Abstract: Endurance and prolonged exercise are altered by hot climate. In hot and dry climate, thermoregulation processes, including evapotranspiration, normally maintain a relatively constant body core temperature. In hot and wet climate (usually called “tropical”), the decrease in evapotranspiration efficacy increases the sweating rate, which can rapidly induce severe hypohydration without efficiently reducing core temperature. The negative effects of tropical environment on long-duration exercise have been well docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…Despite the low temperature of the ingested solution [ 12 14 , 20 , 25 , 26 ] and the additive effect of menthol with cold beverage [ 12 ], our results did not show a significant difference between the Pre-30 condition (i.e., ice-slush/menthol beverage at -1°C during the last 30 min of the resting period) and Neutral condition (i.e., neutral beverage at 23°C during the 1-hour pre-exercise resting period) for performance or rectal temperature. In accordance with other studies [ 19 , 27 ], these results seem to confirm that 30 min of precooling is not enough to improve cycling performance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low temperature of the ingested solution [ 12 14 , 20 , 25 , 26 ] and the additive effect of menthol with cold beverage [ 12 ], our results did not show a significant difference between the Pre-30 condition (i.e., ice-slush/menthol beverage at -1°C during the last 30 min of the resting period) and Neutral condition (i.e., neutral beverage at 23°C during the 1-hour pre-exercise resting period) for performance or rectal temperature. In accordance with other studies [ 19 , 27 ], these results seem to confirm that 30 min of precooling is not enough to improve cycling performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the present data does not support the hypothesis that the use of the cooling bands would have lowered RPE and TS, the present data are to be considered in the context of altered running speed over time. Recent meta-analysis suggests that topical or ingestion of menthol, a known agonist of the “cold receptor,” TRPM8, can alter thermal sensation and/or exercise performance [ 11 ], perhaps independent of core temperature [ 41 ]. Relatedly, work by Phillips et al [ 7 ] suggests that precooling might modulate the prefrontal cortex and/or its processing of afferent feedback regarding perceptions of effort, fatigue, or skin temperature, which might support greater exercise tolerance, and ultimately an attenuation of muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria determined a further removal of 69 articles. Two were review articles (24,25), three had a noncrossover design (26)(27)(28), nineteen reported only physiological, cognitive or perceptual performance measures (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), nine had no control or placebo group (48)(49)(50)(51)(52)(53)(54)(55)(56), five were conference abstracts/posters (57-61), three were performed in clinical context (62)(63)(64), twenty-seven did not report an exclusive effect of the internal cooling and one comprised underage participants (92). Forty-three articles fulfilled the eligibility criteria and data were extracted for qualitative analysis.…”
Section: Literature Searchmentioning
confidence: 99%